Monotheistic understanding of the divine in African religion, Christianity and Islam - EW Namukoa; P Verster; PJ Nel (Acta Theologica)
The article traces the varied expressions of the conception of the Divine in traditional African religion, Islam and Christianity. The focus in particular is on explaining the idea of monotheism in each of these religious traditions. An argument is advanced here that African religion, however different from Christianity and Islam, ultimately also manifests as a form of monotheism. The theological debate on the particular expressions of monotheism in Christianity and Islam also receive attention. Finally, a suggestion is put forward as to the possibility to exploit the commonality of the absolute position of the Divine in the religious traditions as a shared basis for religious tolerance and dialogue.